2011
DOI: 10.5862/mce.26.8
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulics of natural convection flows in building walling with air gap

Abstract: Natural convection flow in vertical flat ducts with heated face is used to intensify the transfer in technical systems, such as ventilated gaps of facade designs. Understanding of physical processes that accompany the air flow in vertical flat parallel-plate ducts gives ameliorating the structures designing process and increasing its operating characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…If width of the gap is reduced, velocity and temperature of air in the gap grows that in one hand improves thermal-humidity conditions of surface, but in the other hand worsens expenditure and water-carrying capacity of the air, and they determine water assimilation ability. Derived results corresponds with data of the works [27,28,29]. 2.…”
Section: Discussionsupporting
confidence: 63%
“…If width of the gap is reduced, velocity and temperature of air in the gap grows that in one hand improves thermal-humidity conditions of surface, but in the other hand worsens expenditure and water-carrying capacity of the air, and they determine water assimilation ability. Derived results corresponds with data of the works [27,28,29]. 2.…”
Section: Discussionsupporting
confidence: 63%
“…Calculations have shown that the moisture-windproof membrane does no affect on the formation of a condensation plane in the outer wall. In the works [17][18][19] it is noted that the speed of air movement in the air gap within the range of up to 30 m is insignificant, which reduces the likelihood of mass emission of insulation fibers.…”
Section: Discussionmentioning
confidence: 99%
“…It is also considered that the particles possess conservative properties in this case i.e. they don't change their chemical characteristics when being transported by the volume of gas [5,6]. Nowadays a number of mathematic models which describe this process are used [9,12,24].…”
Section: Methodsmentioning
confidence: 99%